2022
DOI: 10.1109/tcomm.2022.3165187
|View full text |Cite
|
Sign up to set email alerts
|

A Tb/s Indoor MIMO Optical Wireless Backhaul System Using VCSEL Arrays

Abstract: In this paper, the design of a multiple-input multiple-output (MIMO) optical wireless communication (OWC) link based on vertical cavity surface emitting laser (VCSEL) arrays is systematically carried out with the aim to support data rates in excess of 1 Tb/s for the backhaul of sixth generation (6G) indoor wireless networks. The proposed design combines direct current optical orthogonal frequency division multiplexing (DCO-OFDM) and a spatial multiplexing MIMO architecture. For such an ultra-high-speed line-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…There is a growing interest in OCC because of its applications in V2X communications, indoor positioning, digital signage and VR. FSO communication systems are used for high-data-rate communication in data centers, deep space communication and underwater systems [355], [356]. LiDAR serves as an engaging optical remote sensing technology, and it has great potential to be used for transportation, airborne as well as autonomous vehicular communication.…”
Section: Energy-neutral Devices [338]mentioning
confidence: 99%
“…There is a growing interest in OCC because of its applications in V2X communications, indoor positioning, digital signage and VR. FSO communication systems are used for high-data-rate communication in data centers, deep space communication and underwater systems [355], [356]. LiDAR serves as an engaging optical remote sensing technology, and it has great potential to be used for transportation, airborne as well as autonomous vehicular communication.…”
Section: Energy-neutral Devices [338]mentioning
confidence: 99%
“…This makes their stochastic model different. Despite of all the differences, it is still valid to exploit the intensity distribution of the Gaussian beams in FSO channels [4], and the relation between received power and the incident light direction in VLC channels [15].…”
Section: Available Channel Models and Open Problemsmentioning
confidence: 99%
“…Infrared communication systems are not designed to support illumination so that they can use laser diodes (LDs) as sources to obtain higher speed and narrower beams [3]. Recent studies have reported, with both analyses and experiments, the great potential of applying LD arrays to achieve enormous channel capacity [3], [4]. However, existing studies on indoor infrared communications mainly focused on fixed transceivers and rarely considered the practical issues including mobility and blocking.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this system enables multi-Tb/s aggregate transmission rates over a few meters link by using a 5 × 5 VCSEL array. 10 For each VCSEL, a minimal clipping distortion can be ensured by choosing proper values for the DC bias and the variance of the OFDM signal.…”
Section: Spatial Multiplexing Mimo-ofdm Systemmentioning
confidence: 99%